2006
DOI: 10.1038/sj.mp.4001816
|View full text |Cite
|
Sign up to set email alerts
|

How psychotherapy changes the brain – the contribution of functional neuroimaging

Abstract: A thorough investigation of the neural effects of psychotherapy is needed in order to provide a neurobiological foundation for widely used treatment protocols. This paper reviews functional neuroimaging studies on psychotherapy effects and their methodological background, including the development of symptom provocation techniques. Studies of cognitive behavioural therapy (CBT) effects in obsessive-compulsive disorder (OCD) were consistent in showing decreased metabolism in the right caudate nucleus. Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
1
24

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(276 citation statements)
references
References 69 publications
(89 reference statements)
5
246
1
24
Order By: Relevance
“…More recently, Spironelli and collegues suggested that phonological training might reorganize cortical areas in dyslexic children (Spironelli et al 2010). Furthermore, cognitive behavioral therapy (CBT) techniques have been correlated with neuroplastic changes in different pathological conditions using neuroimaging techniques (Linden 2006;de Lange et al 2008). The potential of MRI techniques to measure CBT impact on brain architecture has been shown also in a recent study on chronic fatigue syndrome patients, in which CBT has been correlated with prefrontal cortex gray matter modulation (de Lange et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Spironelli and collegues suggested that phonological training might reorganize cortical areas in dyslexic children (Spironelli et al 2010). Furthermore, cognitive behavioral therapy (CBT) techniques have been correlated with neuroplastic changes in different pathological conditions using neuroimaging techniques (Linden 2006;de Lange et al 2008). The potential of MRI techniques to measure CBT impact on brain architecture has been shown also in a recent study on chronic fatigue syndrome patients, in which CBT has been correlated with prefrontal cortex gray matter modulation (de Lange et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The definitive version has been published in Criminal Justice, Volume 39, Issue 1, 2011, DOI: 10.1016/j.jcrimjus.2010 CBT is currently the preferred psychosocial intervention in most correctional settings (Sharp, 2006). Linden (2006) reviewed a number of neuroimaging studies that assessed the effects on the human brain of CBT compared with the effects of pharmacological treatment for such maladies as depression and obsessive compulsive disorder. Both types of treatment are found to decrease activity in areas of the brain associated with these problems to the same extent -indicating commonalities in the biological mechanisms of psycho-and pharmacotherapy‖ (Linden 2006:528).…”
Section: Adhd Treatmentmentioning
confidence: 99%
“…Assim, está sendo reconhecido que intervenções psicoterápicas acarretam expressiva modificação nas crenças, nos pensamentos, nas emoções e nos comportamentos dos pacientes (Linden, 2006) e que mudanças nesses níveis estão ligadas a modificações do funcionamento neural (Linden, 2008).…”
Section: Introductionunclassified